Monkeypox 2022 outbreak in non-endemic countries: Open questions relevant for public health, nonpharmacological intervention and literature review - Capobianchi, Maria Rosaria; Di Caro, Antonino; Piubelli, Chiara; Mori, Antonio; Bisoffi, Zeno; Castilletti, Concetta (Frontiers in Cellular and Infection Microbiology, 2022)
Starting from mid-May 2022, cases of human monkeypox started to rise in several non-endemic countries. By mid-July, more than 17000 confirmed/suspect cases have been reported by at least 82 countries worldwide, with a regular incremental trend. In order to contain the disease diffusion, risk evaluation is crucial to undertake informed decisions and effective communication campaigns. However, since orthopoxvirus infections so far have attracted low attention, due to the eradication of smallpox 40 years ago, and to the confinement of human monkeypox almost exclusively to endemic areas, several unresolved issues concerning natural history, ecology and pathogenesis remain. To this respect, we identified some open questions and reviewed the relevant literature on monkeypoxvirus and/or related orthopoxviruses. The results will be discussed in the perspective of their relevance to public health decisions, particularly those related to non-pharmacological interventions.